(untitled) - Naisbitt, John (New York, 1996)
The global axis of power and influence has already shifted from West to East, in his assessment, and the principal trends underlying Asia's rapid modernization include a shift from central government control to free-market economies, the emergence of female entrepreneurs, mass migration to cities and a resurgent individualistic spirit that rejects welfarism. Naisbitt, who has been based in Malaysia for more than a year, peppers this upbeat and optimistic, if shallow, report with sweeping predictions and snap analyses that seem to hit and miss their targets in equal measure. 125,000 first printing
Keywords: Economic forecasting,Asia; Economic conditions; 1945-; Asia